Matlab Use in Design of Digital Systems on the FPGA in CAD Xilinx VIVADO - Свид, І. В.; Мальцев, О. С.; Зубков, О. В.; Сайківська, Л. Ф. (NURE, MC&FPGA, 2019)
Matlab is a high-level language and an interactive environment that can help to analyze data, develop algorithms, create models and applications. There are many extensions for Matlab. One of these extensions is the Xilinx System Generator for DSP, a key component of the Xilinx specialized digital signal processing platform, that allows to implement DSP algorithms with less time costs than traditional RTL design.
Keywords: MATLAB; VHDL; XILINX; VIVADO